Successful Management of Visceral Kaposiform Hemangioendothelioma with Kasabach‐Merritt Phenomenon Using Corticosteroids and Vincristine - Mi Hyeon Gang; Yeon Jung Lim; Mea-young Chang (Korean Society of Neonatology, 2020)
Kaposiform hemangioendothelioma (KHE) is a rare, locally aggressive vascular neoplasm that often develops a coagulopathy known as KasabachMerritt phenomenon (KMP). Visceral involvement denotes a poor prognosis. We report a case of visceral KHE with KMP successfully treated with corticosteroids and vincristine. The infant had been born vaginally at 34 weeks 6 days' gestation, weighing 2,360 g. He was admitted for the management of respiratory failure. Blood tests showed anemia and thrombocytopenia 1 hour after delivery. Additional blood tests revealed a prothrombin time of 12.1 seconds, activated partial thromboplastin time of 60.6 seconds, fibrinogen levels of 72.4 mg/dL, and Ddimer levels >3,200 ng/mL. Despite supportive measures and daily transfusions, the clinical condition and coagulopathy gradually worsened. Renal ultrasonography performed to find the origin of the coagulopathy revealed an echogenic mass measuring >3 cm in the abdominal cavity. A magnetic resonance imaging scan showed an illmarginated, infiltrative mass like lesion in the right anteromedial and posteromedial perirenal space that was hypointense with mild enhancement on T1 and T2weighted images. Large vascular tumors adherent to other visceral organs were noted during exploratory laparotomy but could not be resected. Treatment with methylprednisolone was ineffective. Vincristine was administered weekly from the 17th hospital day, and the coagulation profile showed gradual improvement after its initiation. Intravenous methylprednisolone was switched to oral prednisolone on the 57th hospital day. He was discharged on the 73rd hospital day and continued vincristine treatment every 2 weeks and oral prednisolone administration as an outpatient treatment for 8 weeks. He remained symptomfree at the 39month followup.